DRB-Hicom group managing director appointed as UMP Pro-Chancellor - UMP, PNC
The appointment of DRB-Hicom Group Managing Director, Dato' Sri Haji Mohd Khamil Jamil as Universiti Malaysia Pahang (UMP) Pro-Chancellor was seen as a move that could lead to valuable service and contribution that would be beneficial in enhancing the university's excellence.